Etimologic note: Chalaco - Calvo Pérez, Julio (2011)
This article, or etymological note if preferred, proposes to study the different origins that researchers have given to the word chalaco and its probability management. Thus, it partially supports the etymology proposed by Ricardo Palma and which he later dismissed regarding to the root, chala. It also adds that although the eminent investigator consideresd impossible that it had been born as a derogatory word ending in -aco, the fact is that it has all the chances for having that nasty name. At present, it is an obsolete prejudice as -aco is not longer considered derogatory in this context.